2012
DOI: 10.1002/adsc.201100897
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Hydrosilane Reduction of Ketones Catalyzed by an Iridium Complex Bearing a Hydroxyamide‐Functionalized NHC Ligand

Abstract: An enantioselective hydrosilylation of prochiral ketones was achieved by using a catalytic amount of the readily accessible and air-and moisture-stable iridium complex [IrClA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…For a reaction with a tertiary silane such as R 3 SiH, the reaction appears to proceed by the Ojima mechanism. In the previous report, we showed the hydrosilylation of ketone 5 with Ph 2 SiH 2 catalyzed by IrCl(cod)(NHC) complex 2c furnished a racemic mixture of the reduced product with low yield (36 %) 12b. Therefore, it is likely that the present hydrosilylation with (EtO) 2 MeSiH proceeds through a reaction pathway similar to that proposed by Ojima.…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…For a reaction with a tertiary silane such as R 3 SiH, the reaction appears to proceed by the Ojima mechanism. In the previous report, we showed the hydrosilylation of ketone 5 with Ph 2 SiH 2 catalyzed by IrCl(cod)(NHC) complex 2c furnished a racemic mixture of the reduced product with low yield (36 %) 12b. Therefore, it is likely that the present hydrosilylation with (EtO) 2 MeSiH proceeds through a reaction pathway similar to that proposed by Ojima.…”
Section: Resultsmentioning
confidence: 61%
“…Other ketones 6 – 9 were reduced to their corresponding optically active alcohols with good enantioselectivies at room temperature (Table 2, Entries 2–5). In our previous communication, we had investigated NHC–Ir‐catalyzed enantioselective hydrosilylation of acetophenone derivatives 5 – 9 with (EtO) 2 MeSiH in 2‐methyltetrahydrofuran 12b. A comparison with previously reported results revealed that these substrates, except for 5 and 7 , could be reduced efficiently in the reaction using THF as solvent.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Chiral iridium complexes with hydroxamide‐based tethered NHC ligands, such as 209 , which were originally studied for transfer hydrogenation of ketones, also enable the related asymmetric hydrosilylation of alkyl aryl ketones such as thiophene 212 (Scheme ) . Also, the hydrosilylation of propiophenone ( 214 ) with diethoxy(methyl)silane in the presence of 209 delivers the corresponding alcohol 215 with an e.r .…”
Section: Application In Catalysismentioning
confidence: 99%